Leveraging the agility of the care experience dyad partnership model during COVID-19 - Vanessa Mona; Rana Awdish (The Beryl Institute, 2020)
The extraordinary nature of COVID-19 has presented, and will likely continue to present, unique challenges for care delivery systems; not only in respect to delivery of care to patients, but also in respect to the ways in which health systems care for, and facilitate safe working environments for their employees. It was identified early on that COVID-19 would challenge our Health System, Henry Ford, in its ability to provide an optimal experience of care for our patients. We realized that the feelings of isolation experienced by patients, anxieties experienced by their families and impacts to the well-being of our employees would be significant. Communication was fraught, yet the need for communication had never been greater. Providing difficult news, only to be delivered by phone, injured morale for providers, nurses and support staff. Prior to COVID-19, Henry Ford Health System paired physician and administrative leaders to create high performing dyad partnerships. Clinical and administrative leaders were paired based on their diverse skill sets, competencies and representation. The goals of the Care Experience dyad are to 1) build connectivity; demonstrate support for work being done in times of complex and evolving situations, 2) provide psychological first aid through diffusion and debrief of real time situational stress, utilizing coaching resources, developed by Chief Wellness Officer, 3) assess needs and concerns; assist teams with interpretation and operationalization of rapidly evolving guidelines and protocols; co-discover solutions and escalate concerns, 4) listen with non-judgmental curiosity; normalize and validate feelings and 5) identify and link to resources; identify families who need crisis-level communication. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.